The impact of the use of the obstetric learning model in the teaching of science in the development of scientific concepts and critical thinking among middle third graders in Mecca schools - Alkhayri, Mohammed Hassan (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to reveal the impact of the use of the obstetric learning model in the teaching of science in the development of scientific concepts and critical thinking among middle third graders, To achieve this goal, the experimental approach based on semi-experimental design has been used, The study’s tools consisted of testing scientific concepts by the researcher, and Watson and Schleser’s critical thinking test - the short picture, They were applied to a random sample of 86 middle-third graders in Mecca, Represented in (44) students of the pilot group and (42) students of the control group, The results of the scientific concept test showed that the experimental group obtained a total average (29.23 out of 40) while the officer obtained an average (20.41 out of 40) in the remote application, In the critical thinking test, the experimental group received a total average (33.68 out of 40), The officer received an average (23.86 out of 40) and a statistically d difference at the level (α≤0.05) between the average experimental and controlling groups and in favor of the pilot, The ETA box (²η) was valued at impact size (0.76, 0.83) each, respectively. It reflects the magnitude of the impact (very large) of the independent variable, and there is no statistically significant correlation between the overall degree of testing of scientific concepts and the overall degree of critical thinking testing in the remote application of students in the experimental group, In light of the findings of the study, the researcher recommended the need to pay attention to the model of obstetric learning as an important entry point in the education and learning of science, and other scientific materials at different levels of study and in all schools in the Kingdom.